Solids transport modeling in a fluidized drum granulator - Rojas Ardiles, Rodrigo Jovan (2010)
The fluidized-bed granulator (FDG) involves the use of a fluidized bed in a drum granulator, which is a horizontal cylinder fitted with internal flights. Despite its demonstrated success on an industrial scale, there are few published fundamental studies of this granulation process. In this work, a mathematical model to represent the solids flow pattern within the different active and passive zones of the rotating FDGs is developed. The fluidization table geometry as well as the angular velocity, drum inclination angle, and flights number strongly affect the mass holdups. Relatively high rotational speeds, inclination angles, and number of flights allow increasing the active mass holdups, reducing the passive mass, and eliminating the kilning flow. The model presented in this work, which accounts for the solids mass flows and holdups in the different zones of a FDG, provides a firm foundation for integration with energy and population balances.